Re-greening Ethiopia: history, challenges and lessons - Lemenih, H; Kassa, H. (MDPI, 2014)
In Ethiopia, deforestation rates remain high and the gap between demand and domestic supply of forest products is expanding, even though government-initiated re-greening efforts began over a century ago. Today, over 3 million hectares (ha) of degraded forest land are under area exclosure; smallholder plantations cover 0.8 million ha; and state-owned industrial plantations stagnate at under 0.25 million ha. This review captures experiences related to re-greening practices in Ethiopia, specifically with regards to area exclosure and afforestation and reforestation, and distills lessons regarding processes, achievements and challenges. The findings show that farmers and non-governmental organizations (NGOs) are the main players, and that the private sector has so far played only a small role. The role of the government was mixed: supportive in some cases and hindering in others. The challenges of state- and NGO-led re-greening practices are: inadequate involvement of communities; poorly defined rehabilitation objectives; lack of management plans; unclear responsibilities and benefit-sharing arrangements; and poor silvicultural practices. The lessons include: a more active role for non-state actors in re-greening initiatives; more attention to market signals; devolution of management responsibility; clear definition of responsibilities and benefit-sharing arrangements; and better tenure security, which are all major factors to success.